TINJAUAN YURIDIS SOSIOLOGIS PERLINDUNGAN HUKUM BAGI ANAK JALANAN YANG BEKERJA DI SEKTOR INFORMAL STUDI DI KOTA TANGERANG SELATAN - SANTINI, INAWATI; Sicillia, Mita (Jurnal Ilmiah Hukum dan Keadilan, 2023)
Child labor is increasing where many children enter an institution or agency to do a job, the question that is often raised is whether children actually have the right to work, whether or not children have the right to work must be taken seriously and carefully. Jobs in Indonesia are always opened both formally and informally, the problem is that there is still a legal relationship that exists between the child and a certain agency or institution based on the existence of a working relationship between the two parties, in which the child is represented by the parent or guardian either by virtue of a work agreement verbally or in writing or consciously or unconsciously the child's parents make the child's decision to work. Social conditions cause children to generally work informally because the main capital for work does not demand special or specific requirements, the most important thing is determination, willingness and sincerity to work. so that this becomes an opportunity for children to work in certain sectors. Supervision of child workers should be a top priority, so that the protection of children's rights can be realized as a form of state responsibility. This problem is trying to be studied how Juridical Sociological Review of Legal Protection for Street Children Working in the Informal Sector (Study in South Tangerang City). By using normative legal research methods and qualitative approaches, it is hoped that this paper can answer these problems